The Influence of Individual Characteristics and Work Experience on Work Ethic - Habibi Habibi; Firmansyah Firmansyah (BJRM (Bongaya Journal of Research in Management), 2022)
This study aims to determine wheter Individual characteristics and work experience affect the work ethic of employees at the marine and fisheries department of shouth Sulawesi province. Data collection uses primary data using a questionnaire technique. The population is the entire marine and fishery department of south Sulawesi province totaling 207. While the sample taken is 67 employees using the slovin formula. The result of the questionnaire have been tested for validity and reliability. And classical assumptions have been tested in the form of normality assumptions. Heteroscedasticity assumptions and multycollinearity. The method of data analysis used multiple regression analysis techniques.The result of the research shows that individual characteristics have a positive and significant effect on the employees work ethic. Work experience has a positive and significant effect on the work ethic of employees. And simultaneously individual characteristics and work experience have a positive and significant effect on the work ethic of employees